Karakteristik Tafsîr Al-Qur’ân Al-Karîm Karya Mahmud Yunus - Sulaiman Ibrahim (Al-Ulum, 2011)
The ‘Tafsîr al-Qur'ân al-Karîm’ is the result of investigation for at least fifty-three years, ie since the author was 20 years old to 73 years. This interpretation is among of masterpiece work of Mahmud Yunus who has orientation to explain and clarify the instructions contained in the Koran for practiced by Muslims in particular and mankind in general, as a universal guide. The exegesis of 30 juz of the Koran is a work of translation is the most comprehensive one in his time. The comprhensi-onsiveness is due to two things: first translation is done no longer a separate part of the verses or surah-specific chapters, as shades of interpretation in the first generation; and second is the statement-information in the form of footnotes as a complement to provide pemaharnan on the meaning of certain verses.